A implementação de inovações originadas de um programa de geração de ideias de uma instituição financeira - Ida, Lucas Makoto Conchon (2020)
This study investigated the implementation of innovations originating from an idea generation program in a financial institution. The investigation method was the Case Study. The unit of analysis was the Idea Generation Program (IGP) of a bank that has already received several awards for the innovations it has generated. The main criteria for choosing the unit of analysis were the relative maturity of the IGP, carried out fourteen years ago, the presentation of concrete results of innovation since its first edition, the receipt of approximately twenty thousand ideas from employees, the highlight in reports business magazines and the link to the company corporate strategy. The results were described from three theoretical lenses of the Evolutionary Theory of Innovation and demonstrate that the innovations generated from the IGP were predominantly incremental in services and in business processes. In particular, an innovation in services generated financial returns of approximately five billion Reais. The results indicated that the idea generation program generated benefits beyond technological innovation, such as strengthening the culture of innovation in the organization. The results also demonstrate that it is necessary to make good decisions in the implementation or improvement of the idea generation program, as the decisions made may incur the success or failure of the program. In addition, they demonstrated that financial, people and time investment is essential to generate innovations that lead the company to survive or gain competitiveness in the market. It was concluded that the idea generation program can be useful to innovate, as long as it is well structured, has clear rules and investment in people, time and finance is already allocated before the start of the process. It was also concluded that the promotion of the culture of innovation can be one of the main results of an Idea Generation Program, this being one of the contributions originated from this research. In addition, it was concluded that the idea implementation phase is the most critical phase of the Idea Generation Program. The most prominent limitation is of a methodological nature and is related to the research profile and its borders, such as the choice of participants and the respective unit of analysis. There are also theoretical limitations that refer to the exploration of Idea Generation Programs. For future studies, multiple case studies are suggested in companies from different sectors of the economy that already have Idea Generation Programs in place. Another suggestion is to conduct research with a quantitative and qualitative approach on the results of innovations generated in organizations or studies that investigate the use of information technologies to support the management of Idea Generation Programs.